Social Capital and the Uncertainty Reduction of Self-Employment - Boris F. Blumberg; Gerard A. Pfann (Institute for the Study of Labor (IZA), 2001)
We study the self-employed decision and its relation to human and social capital. Human capital is necessary to acquire skills. Social capital dampens the effects of uncertainty about future income. Our data set consists of 1339 respondents from the same age group, who were interviewed three times in life in 1957, 1983 and 1993. The self-employment probability equals 155 and peaks between ages 24 and 26. Duration analysis shows that social capital is the most important resource for self-employment.
Keywords: J23; 330; Self-employment; social capital; human capital; event history; Selbstständige; Unternehmensgründung; Humankapital; Social Capital; Verdienstausfall; Schätzung; Niederlande